Раскопки на селище салтово-маяцкой культури у с. Давыдо-Никольское - Красильников, К.И.; Красильникова, Л.И. (Археологічні дослідження в Україні, 2010)
In 2009, at the settlement of Saltovo-Mayak culture near Davydo-Mykilske village in the Siverskyi-Donets River region the yard and other objects of husbandry and manufacture functions were discovered.